Penekanan Penyakit Blas Leher Malai Padi Menggunakan Ekstrak Kompos Jerami Padi - Suwandi Suwandi; Harman Hamidson; Ahmad Muslim (Jurnal Fitopatologi Indonesia, 2016)
Blast is the most important disease of rice and may cause significant losses in the reclaimed tidal swamp of South Sumatra. Water extracts of fermented composts prepared from straws of the vigorous rice plant were tested in pot experiment for their ability to control blast. Rice variety Ciherang was grown on mixture of field soil and 1% diseased rice straw (v/v) collected from a tidal swamp rice field. Incidence of panicle blast was reduced by 71−87% in response to application of compost extract. The compost extract did not affect seed germination and plant height, instead, it increased the yield. The rice straw from healthy and vigorous plants is potential as a source for blast disease control.